2005
DOI: 10.1158/1055-9965.epi-05-0316
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Inflammatory Markers and Cancer Risk in the Health Aging and Body Composition Cohort

Abstract: Background: Chronic inflammation is associated with processes that contribute to the onset or progression of cancer. This study examined the relationships between circulating levels of the inflammatory markers interleukin-6 (IL-6), Creactive protein (CRP), and tumor necrosis factor-A (TNF-A) and total as well as site-specific cancer incidence. Methods: Study subjects (n = 2,438) were older adults (ages 70-79 years) participating in the Health Aging and Body Composition study, who did not report a previous canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
349
6
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(386 citation statements)
references
References 43 publications
28
349
6
3
Order By: Relevance
“…Studies have demonstrated that the levels of proinflammatory cytokines were increased in systemic circulation of patients diagnosed with prostate cancer [21][22][23]. We have previously demonstrated the The Prostate DOI 10.1002/pros Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have demonstrated that the levels of proinflammatory cytokines were increased in systemic circulation of patients diagnosed with prostate cancer [21][22][23]. We have previously demonstrated the The Prostate DOI 10.1002/pros Fig.…”
Section: Discussionmentioning
confidence: 90%
“…For reporting different cancer type, both studies of Zhang et al (2007) and Zhang et al (2005) were inclusive, although their participants were from the same population. At last, 10 articles (Il'Yasova et al, 2005;Zhang et al, 2005;Siemes et al, 2006;Zhang et al, 2007;Allin et al, 2009;Heikkila et al, 2009;Pierce et al, 2009;Dos et al, 2010;Prizment et al, 2011;Van et al, 2011) including 11 cohort studies were eligible for inclusion criteria in this meta-analysis (one article including two separate cohorts (Heikkila et al, 2009)), involving a total of 194,796 participants and 11,459 cancer cases. Table 1 summarizes the baseline characteristics of 11 cohort studies included.…”
Section: Resultsmentioning
confidence: 99%
“…In studies of Van et al (2011) and Siemes et al (2006) where HR was reported based on various length of followup, the HR with the longer follow-up was used to compute. The results of a pooled analysis in all 11 included cohort studies (Il'Yasova et al, 2005;Zhang et al, 2005;Siemes et al, 2006;Zhang et al, 2007;Allin et al, 2009;Heikkila et al, 2009;Pierce et al, 2009;Dos et al, 2010;Prizment et al, 2011;Van et al, 2011) are shown in Figure 2. The overall pooled HR per natural log unit change in CRP for all-cancer was 1.105 (95% CI: 1.033-1.178), with substantial heterogeneity amongst studies (P heterogeneity =0.000, I 2 =70.10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several small case-control studies have suggested serum IL-6 is increased in women with breast cancer [14]. Recently, Il'yasova et al [15] reported increased serum CRP was associated with incident breast cancer in a cohort of post-menopausal women. Polymorphisms in the IL6 gene promoter, −572G/C and the -174G/C, have been reported to be related to levels of circulating CRP [16] and to breast cancer [17].…”
Section: Introductionmentioning
confidence: 99%